Relevansi Delik Pengancaman dalam Penyelesaian Utang Piutang terhadap Pertanggungjawaban Pidana Pelaku (Studi Putusan Nomor: 1221/Pid.B/2024/PN TJK) - Benny Karya Limantara; Dicky Kurniawan (AHKAM, 2026)
Although the criminal offense of threats has been extensively examined in criminal law scholarship, studies that specifically explore its relevance in the context of debt settlement and its relationship to the offender’s criminal liability remain relatively limited. In judicial practice, debt disputes frequently escalate into criminal cases due to the use of threats as a means of debt collection, thereby necessitating more in-depth analysis. This study aims to analyze the relevance of the offense of threats in the settlement of debt and credit relationships and the criminal liability of the offender based on Decision Number 1221/Pid.B/2024/PN Tjk. A qualitative approach was employed with a normative legal research design and case study strategy, using primary, secondary, and tertiary legal materials selected through purposive sampling. Data were collected through library research and document study of court decisions and relevant legislation, then analyzed using descriptive juridical and argumentative juridical analysis. The findings show that although the case originated from a civil legal relationship in the form of debt and credit, the defendant’s conduct fulfilled the elements of the offense of threats as stipulated in Article 335(1) of the Indonesian Criminal Code (KUHP), thereby justifying the imposition of criminal liability on the perpetrator. These findings contribute to strengthening the theory of criminal liability and clarifying the boundary between civil disputes and criminal acts. The study concludes by emphasizing the importance of caution in the use of criminal law to avoid the criminalization of civil disputes while ensuring adequate legal protection for victims, and it opens opportunities for further research through empirical approaches and comparative analysis of court decisions.